Enantiopure Conducting Salts of Dimethylbis(ethylenedithio)tetrathiafulvalene (DM‐BEDT‐TTF) with the Hexachlororhenate(IV) Anion. Issue 24 (August 2014) - Pop, Flavia; Allain, Magali; Auban‐Senzier, Pascale; Martínez‐Lillo, José; Lloret, Francesc; Julve, Miguel; Canadell, Enric; Avarvari, Narcis
Abstract: Invited for the cover of this issue is the group of Narcis Avarvari (CIMI team) at the Laboratory MOLTECH‐Anjou, UMR 6200 CNRS – Université d'Angers, France. The cover image shows the enantiopure tetrathiafulvalene precursors used for the preparation of chiral radical cation conducting salts, together with an artwork of their packing diagrams and the suggested mirror image relationship between them. Abstract : We have recently obtained one of the most important results in the field, with the first observation of the eMChA effect in chiral bulk molecular conductors... Read more about the story behind the cover in the Cover Profile and about the research itself onp. 3855 ff .